Pengaruh Strategi Metakognitif terhadap Efikasi Diri dan Pemecahan Masalah Siswa MAN 2 Mojokerto: The Influence of Metacognitive Strategies on Self-Efficacy and Problem Solving of Students at MAN 2 Mojokerto - Rodli, Moh; Widiastutik , Trisya (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Research objective of the study is to know the influence of metacognitive strategies to the self-efficacy and problem solving of MAN 2 Mojokerto students'. Research design used? in study was quasi experiment with technique? of data analysis in the form of analysis multiple linear regression. It is also used prerequisite tests regression which includes the normality test, multicollinearity test, and heteroscedasticity test, as well as hypothesis testing which includes the simultaneous test (F), partial test (t), and coefficient determination (R2). Based on results statistics using Two Way ANOVA SPSS then it can be concluded that metacognitive strategy has a significant influence on self- efficacy, but on the other hand it can not give significant influence? to problem solving abilities